Impact of Arbuscular mycorrhizal Fungal Strains Isolated from Soil on the Growth, Yield, and Fruit Quality of Tomato Plants under Different Fertilization Regimens - Wissame Chafai; Kaoutar Haddioui; Hana Serghini-Caid; Hicham Labazi; Mashail N. AlZain; Omar Noman; Mohammad Khalid Parvez; Mohamed Addi; Ahmed Khalid (Horticulturae, 2023)
Arbuscular mycorrhizal fungi (AMF) have emerged as a promising and environmentally friendly solution for sustainable agriculture, offering a reduction in dependence on chemical inputs. The objective of this greenhouse experiment was to assess the efficacy of a natural endomycorrhizal inoculum obtained from leek root fragments, which acted as a trap plant to capture indigenous fungal spores present in the soil of the Guercif region in Morocco. The investigation aimed to comprehensively evaluate the influence of this inoculum on various parameters related to tomato plant growth, yield, and sensory quality. Additionally, different levels of chemical fertilizers, equivalent to 50%, 75%, and 100% of the recommended dosage, were administered in combination with or without the inoculum. The findings elucidated significant advantages associated with mycorrhizal inoculation. The plants subjected to inoculation exhibited increased plant height, augmented leaf and root dry weights, and improved nutrient uptake compared to the control group. Notably, tomato plants treated with 75% of the recommended chemical fertilizer dosage yielded the highest crop production, with no statistically significant difference observed when compared to those receiving the full dosage (100%). Intriguingly, tomato plants grown in substrates receiving 50% chemical fertilizers demonstrated the highest levels of mycorrhization, exhibiting a frequency (F) of 100% and an intensity (M) of 63%. Importantly, the combination of inoculation with a reduced dose of NPK fertilizer (50% of the recommended amount) resulted in significantly elevated concentrations of calcium (Ca), potassium (K), iron (Fe), zinc (Zn), and phosphorus (P) in the plants, attributable to the heightened mycorrhizal colonization of the roots. In terms of fruit characteristics, no significant variations were detected in pH and electrical conductivity (EC) among the treatment groups. However, the inoculated plants exhibited a notable increase in the Brix index, an indicator of sweetness, compared to the control group across all fertilizer doses. Furthermore, inoculation positively influenced the levels of total carotenoids in the fruits. Remarkably, the values of these compounds in the inoculated plants subjected to 50% of the recommended fertilizer dosage surpassed those recorded in the non-inoculated plants receiving the full dosage.